2020
DOI: 10.13106/jafeb.2020.vol7.no12.627
|View full text |Cite
|
Sign up to set email alerts
|

Firm’s Risk and Capital Structure: An Empirical Analysis of Seasonal and Non-Seasonal Businesses

Abstract: The study attempts to analyze the impact of firm's risk on capital structure in the context of seasonal and non-seasonal businesses. We use two independent variables namely credit risk and systematic risk and one dependent variable to explore this connection. Sugar sector is taken as seasonal while the textile sector as non-seasonal businesses. The panel data of twenty-five firms from each sector are taken ranging for the period of 2012 to 2019 which has been retrieved from their annual reports for empirical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
1
1
Order By: Relevance
“…Our results also conform to the results of Fahlenbrach et al (2012) and Acharya et al (2013), who found that stock returns were lower for banks with highly illiquid assets. However, our finding contradicts those of Amir and Nejad (2018), Qin and Zhou (2019), Jaafar et al (2020), Tripathi andThukral (2018), andTahir et al (2020). They proved the significant influence of leverage on systematic risk.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results also conform to the results of Fahlenbrach et al (2012) and Acharya et al (2013), who found that stock returns were lower for banks with highly illiquid assets. However, our finding contradicts those of Amir and Nejad (2018), Qin and Zhou (2019), Jaafar et al (2020), Tripathi andThukral (2018), andTahir et al (2020). They proved the significant influence of leverage on systematic risk.…”
Section: Discussioncontrasting
confidence: 99%
“…Jaafar et al (2020) showed that leverage and growth are the most significant factors of the systematic risk of Shariah-compliant firms. Tripathi and Thukral (2018) and Tahir et al (2020) also proved the significant linkage between systematic risk and leverage.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 86%
“…In this research object, the decline in capital structure was followed by a decrease in credit risk as in Bank Capital Indonesia Tbk in 2018 the value of DER (11,135) increased in 2019 (11,330) followed by the value of NPL in 2018 (2,954%) increased in 2019 (3,480%). Tahir et al (2020) and H. A. Putra (2014) said that capital structure and credit risk are very important in financing decision making.…”
Section: The Effect Of Capital Structure On Credit Riskmentioning
confidence: 99%
“…Based on this, companies with high business risk will try to maintain their debt portion not to endanger the company's sustainability. Based on research conducted by (Tahir et al, 2020) they are stated that business risk affects capital structure.…”
Section: Growth Opportunitymentioning
confidence: 99%